PENENTUAN HARGA KAIN TENUN PADA DESA SALUALLO KEC.SANGALLA UTARA , KAB. TANA TORAJA - Selvi Yanti Patintingan; Natalia Paranoan; Erna Pasanda (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2019)
Determining the Price of Woven Fabrics in Saluallo Village, Kec. Sangalla Utara, Tana Toraja Regency. This research is a field research and literature using a qualitative descriptive method, which aims to determine the price of woven fabric in the Saluallo Village, Kec.Sangalla Utara, Kab.Tana Toraja. Data collection techniques are observation, interviews, and documentation. This research was conducted by interviewing informants in this case weaving craftsmen and woven fabric collectors to find out how the price of woven fabrics among weaving craftsmen and among collectors. The results showed that the price of woven cloth was determined by factors of raw material costs, direct labor costs and factory overhead costs, for the determination of fair prices.